Promoting global sustainable development: spatial spillover effects of higher education on economic and ecological sustainability - Daozheng Li; Xiaoxiao Sun; Tongning Li (Discover Sustainability)
Abstract Higher education plays an important role in promoting sustainable ‘economic-ecological’ development. In this paper, we selected 22 indicators to construct three core measures of ecological, economic, and higher education quality for 61 sovereign countries from 2000 to 2022. Utilizing Ecosystem Service Values, entropy weighting method, and coupled coordination model, and constructed a double-fixed spatial Durbin model to measure the impact of higher education on the global economic-ecological sustainable development and spatial spillover effects. It is found that in Europe the rise in the comprehensive level of higher education is not significant for the improvement of the sustainable development of the country, and it mainly enhances the sustainable development level of neighboring countries through the interactive flow; while in other regions, such as Asia, the rise in the comprehensive level of higher education will significantly improve the level of sustainable development in the region, but there is a significant siphon effect, which will inhibit the development of the neighboring regions by pooling the talents, funds, and technologies through its development inhibit the development of neighboring regions. In addition, the promotion effect of higher education on regional sustainable development has a diminishing marginal utility and gradually converges to be no longer significant.